American Medical Society for Sports Medicine Position Statement: Principles for the Responsible Use of Regenerative Medicine in Sports Medicine. Issue 6 (November 2021) - Finnoff, Jonathan T.; Awan, Tariq M.; Borg-Stein, Joanne; Harmon, Kimberly G.; Herman, Daniel C.; Malanga, Gerard A.; Master, Zubin; Mautner, Kenneth R.; Shapiro, Shane A.
Abstract : Abstract: Many sports medicine physicians are currently considering introducing regenerative medicine into their practice. Regenerative medicine and the subclassification of orthobiologics are a complicated topic and have produced widely varying opinions. Although there is concern by government regulators, clinicians, scientists, patient advocacy organizations, and the media regarding the use of regenerative medicine products, there is also excitement about the potential benefits with growing evidence that certain regenerative medicine products are safe and potentially efficacious in treating musculoskeletal conditions. Sports medicine physicians would benefit from decision-making guidance about whether to introduce orthobiologics into their practice and how to do it responsibly. The purpose of this position statement is to provide sports medicine physicians with information regarding regenerative medicine terminology, a brief review of basic science and clinical studies within the subclassification of orthobiologics, regulatory considerations, and best practices for introducing regenerative medicine into clinical practice. This information will help sports medicine physicians make informed and responsible decisions about the role of regenerative medicine and orthobiologics in their practice.